Murine epidermal Langerhans cells express significant amounts of class I major histocompatibility complex antigens. - Lenz, A (1989)
Epidermal Langerhans cells (LC) are leukocytes that express major histocompatibility complex (MHC) class II antigens and function as antigen-presenting and accessory cells. Caughman et al. [Caughman, S. W., Sharrow, S. O., Shimada, S., Stephany, D., Mizuochi, T., Rosenberg, A. S., Katz, S. I. & Singer, A. (1986) Proc. Natl. Acad. Sci. USA 83, 7438-7442] reported that LC are deficient in surface expression of MHC class I antigens, implying a specialization of these cells to class II-restricted antigen presentation. To readdress this obviously important issue, we have studied murine epidermal sheets prepared from B6 X BALB/c----B6 bone marrow chimeras 5 months after irradiation and bone marrow reconstitution. This enabled us to distinguish class I of LC from that of surrounding keratinocytes. When sheets were analyzed by immunofluorescence microscopy with monoclonal antibodies specific for donor class I antigens, donor-derived LC but not LC of recipient origin were stained. Appropriate controls for antibody isotype and MHC haplotype were negative. LC in epidermal cell suspensions, prepared from normal BALB/c and BALB/cBy mice (MHC haplotype d), were analyzed by flow cytometry as well as immunofluorescence microscopy. LC were stained by monoclonal antibodies to class I antigens of haplotype d, but not by isotype-matched control antibodies to class I antigens of haplotype k. We also found that LC were virtually depleted from epidermal cell suspensions by treatment with monoclonal antibodies to class I antigens of haplotype d and complement but not by treatment with control monoclonal antibodies and complement. Our data, therefore, show that LC express MHC class I molecules on their surface.